(3ESJQGJjLjGJ GdJehjd aj GdeDSSGJ GdGbJUGOjIs - (3ehdhO(B, (3edjcGhjs ((3GdLRGFQ(B:s (3OGQ gheI(B,s, 2019)
(3JfGhd gPG GdcJGH ESJQGJjLjGJ GdJehjd aj GdeDSSGJ GdGbJUGOjI, MjK JMOK ef NdGd aUhd OQGSJg Yf GdCShGb hGdeDSSGJ GdeGdjI, hGdhXjaI GdeGdjI aj GdeDSSI GdGbJUGOjI, HGdGVGaI Gdi GdJehjd hGdSjGSGJ GdJehjdjI heUGOQgG bUjQI GdCLd hWhjdI GdCLd, cPdc JMOK Yf eUGOQ GdJehjd GdPGJj h GdJehjd HGdGSJFLGQ, hYf WQjb JMhjd GdaGJhQI , hGdJehjd Yf WQjb QCS GdeGd GdeNGWQ, hJcdaI QCS GdeGd, HGdGVGaI Gdi GdYhGed GdeMOOI ddgjcd GdeGdj, hGdQaY hGdbQGQ GdJehjdj, hCNjQG fXQGJ gjcd QCS GdeGd GdCeKd(B. s
(3eQGLY U(B.259s
Keywords: (3GdJehjds; (3GdeDSSGJ GdEbJUGOjIs